Spectroscopic and Docking Studies on the Binding of Liquiritigenin with Hyaluronidase for Antiallergic Mechanism - Hua-jin Zeng; Ran Yang; Jing You; Ling-bo Qu; Yan-jun Sun (Scientifica)
The inhibitory effect of liquiritigenin on hyaluronidase and its binding mechanism were investigated systematically by UV-vis absorption, fluorescence, and molecular modeling approaches. These results indicated that liquiritigenin could interact with hyaluronidase to form a liquiritigenin-hyaluronidase complex. The binding constant, number of binding sites, and thermodynamic parameters were calculated, which indicated that liquiritigenin could spontaneously bind with hyaluronidase mainly through electrostatic and hydrophobic interactions with one binding site. Synchronous fluorescence, three-dimensional fluorescence, and molecular docking results revealed that liquiritigenin bound directly to the enzyme cavity site and this binding influenced the microenvironment of the hyaluronidase activity site, resulting in reduced hyaluronidase activity. The present study provides useful information for clinical applications of liquiritigenin as a hyaluronidase inhibitor.